Ways of perfection of activity of representative organs On local self-government in Ukraine - Заяць, Наталія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
Problem directions of activity of organs of local self-government as representative are considered in the article, and also realizable attempt of formulation of legislative ways of their perfection. In particular making alteration is offered in Law of Ukraine "On local self-government" in relation to perfection of legal status of chairman of local advice as representative organ.